Genetic spectrum of Kallmann syndrome: Single‐center experience and systematic review. (30th September 2022) - Patil, Virendra A.; Lila, Anurag Ranjan; Shah, Nalini; Arya, Sneha; Sarathi, Vijaya; Shah, Ravikumar; Jadhav, Swati S.; Memon, Saba Samad; Karlekar, Manjiri; Bandgar, Tushar
Abstract: Objective: To study phenotype‐genotype data of Asian−Indian Kallmann syndrome (KS) from our center and systematically review the studies analyzing multiple congenital hypogonadotropic hypogonadism (CHH) genes in KS cohorts using next‐generation sequencing. Design, Patients, Measurement: Five hundred twenty‐two KS probands (our center n = 78, published studies n = 444) were included in this systematic review. Molecular diagnosis was considered if the likely pathogenic/pathogenic variant in known CHH gene/s was reported in the appropriate allelic state. Varsome prediction tool (following American College of Medical Genetics standards) was used to analyze the variants. Result: For our center, the molecular diagnosis was seen in 20.5% of probands and was seen more often with severe than partial reproductive phenotype (28.3% vs. 4%, p = .0013). Our center data adds eight novel variants. The molecular diagnosis was seen in 31% as per the systematic review and analysis. It ranged from 16.6% to 72.2% at different centers. The affected genes were FGFR1 (9.8%), ANOS1 (7.5%), PROKR2 (6.1%), CHD7 (5.4%), oligogenic (2.1%), and others <1% each ( FGF8, SOX10, PROK2, SEMA3A, IL17RD, and GNRHR ). FGFR1 and ANOS1 were the commonly affected genes globally, whereas PROKR2 was commonest in studies from China and CHD7 from Japan, South Korea and Poland. Conclusion(s): This systematic review highlights that the genetic yield is 31% in KS probands, with distinct regional variations. The association of severe reproductive phenotype with the higher genetic yield needs further validation.